2000
DOI: 10.1002/pen.11340
|View full text |Cite
|
Sign up to set email alerts
|

The production of a new partially biodegradable starch plastic by reactive extrusion

Abstract: The grafting of polystyrene onto dissolved starch in a twin screw extruder has been studied. This copolymerization was initiated using the thermal initiators benmy1 peroxide and K&O,. As end product a mixture containing polystyrene-grafted starch, homopolymer of polystyrene and starch was obtained. Parameters like screw rotation rate, fully filled length of the extruder, wall temperature and throughput have been varied in order to obtain information about their influence on conversion, graft percentages and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…Calender rolls are widely used in the production of poly(vinyl chloride) sheet and film (Robertson 1993). Studies on extrusion of certain biopolymers such as starch, soy protein, and caseinate (Mungara and others 1998; De Graaf and Janssen 2000; Fossen 2000; Li and Lee 2000; Nabeshima and Grossman 2001) suggest the possibility of extruding whey proteins to form films.…”
Section: Introductionmentioning
confidence: 99%
“…Calender rolls are widely used in the production of poly(vinyl chloride) sheet and film (Robertson 1993). Studies on extrusion of certain biopolymers such as starch, soy protein, and caseinate (Mungara and others 1998; De Graaf and Janssen 2000; Fossen 2000; Li and Lee 2000; Nabeshima and Grossman 2001) suggest the possibility of extruding whey proteins to form films.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, possibilities to blend with lower-priced starch are being studied. [3][4][5][6] Past studies have shown that the amount of starch blended with plastics is relatively small and the dynamic properties are not sufficient. It is necessary to modify ordinay starch, which has inferior mechanical characteristics compared with the general-purpose plastics, such as poly(ethylene) and poly(propylene).…”
Section: Introductionmentioning
confidence: 99%
“…Few additives having hydrophilic groups, make plastic hydrophilic and susceptible for photo and chemical degradation. Modification of plastic through copolymerization and through anchoring monosaccharide into it or blending with nutrients and biodegradable fillers makes it degradable [11][12][13][14] . These micronutrients help the growth of specific microorganisms and this incorporation of polar functional groups can serve as point for microbial attack [15] .…”
Section: Introductionmentioning
confidence: 99%